The Very Best People: President Trump and the Management of Executive Personnel. Issue 1 (17th January 2021) - Lewis, David E.; Richardson, Mark D.
Abstract: To his supporters, one very attractive feature of Donald Trump's candidacy was his prior experience as a business executive. Trump promised that he would run America like a business and would select the very best people. In this article, we evaluate President Trump's approach to managing the executive branch by scrutinizing his approach to personnel. We reference two sources of important new data. We first examine data on nominations to all Senate‐confirmed positions during the last three presidencies. We also use data from the 2007, 2014, and 2020 (preliminary) Surveys on the Future of Government Service, surveys of thousands of appointed and career federal executives, to determine whether the president selected the very best people. We conclude by using the survey data to evaluate whether the president's approach led to effective management. A close look at the new data reveals that the president has been slow to nominate officials to key positions. Federal executives rate the persons the president has appointed as less competent than appointees from the Bush administration or civil servants from the current one. The survey data also reveal that the president's approach has done nothing to arrest the decline in the capacity of the public service. We conclude by discussing the implications of the Trump presidency for our traditional understanding of the president as chief executive. Specifically, we discuss whether we should reevaluate common beliefs about presidents caring inherently about the management of the executive.